Aporte de la auditoria de sistemas a la implementación de la interoperabilidad del sistema de recaudo electrónico vehicular (IP-REV) definido por el ministerio de transportes para los peajes de colombia (2022)
The Ministry of Transport undertook an interoperability project, and granted a deadline of October 2022. The study aims to answer the question: What are the technical and interoperability specifications required by the Ministry of Transport to certify that the Road and Toll Concessionaire Does it have a technological and computer infrastructure for the Implementation of the IP/REV in the tolls of Casablanca, Oiba, Curití, Curos and Saboyá? It is justified because the product adds value and benefits the stakeholders to know the main items that give rise to understanding, identify technological risks and propose a system audit model that allows mitigating the risks that could arise in the implementation of the electronic system. (IP-REV), to achieve the objective of the project. The theoretical reference focused on the Contractual Obligations, the Regulations such as Laws 80/1993 and 1508/2012, in addition to the background, and technical requirements defined by the Mintransporte for the IP/REV. In order to carry out a systems audit for the implementation of the IP/REV in the tolls of Casablanca, Oiba, Curití, Curos and Saboyá, it is necessary to apply a methodology such as that provided by the ISO 31000 standard (Risk management) and the NTC 5254 standard that provides the guidelines for its realization, in addition to carrying out field and documentary research that contributes to the knowledge of the contexts associated with the operation of interoperability of tolls and the use of procedures, techniques and systems audit tools to carry out the audit